Population Assessment of Trichoderma piluliferum Using a Modified Selective Medium - Joshi, Kirti; Harsh, N. S. K. (Indian Forester, 2009)
Trichoderma species are one of the potential biocontrol agents exploited to manage many of the soil and seed borne plant pathogens. Quantitative estimation of Trichoderma species in soil is often difficult because of relatively rapid growth of other soil fungi on conventional agar media, so selective medium is required for isolating Trichoderma from soil as well as for estimating its survival in soil. Various media and different combinations have been tried for making dilution plates of Trichoderma from soil. This study was taken up to prepare the most effective selective medium which contained Magnesium sulphate (0.2 g), Potassium orthophosphate (0.9 g), Ammonium nitrate (1.0 g), Potassium chloride (0.15 g), Glucose (3.0 g), PCNB (0.1 g), Rose Bengal (0.1 g), Chloramphenicol (0.25 g), Agar (15 g), Metalaxyl (0.1 g) and Distilled water (1 lit).